The choice of the method and technical means for the automatic control of the insulation thickness of the frames in the winding process - Seydaliyev, Ilham Mohammed (Eastern-European Journal of Enterprise Technologies, 2020)
The existing problems in the field of controlling the insulation thickness of cylindrical frames in the process of automatic winding are shown. Methods of controlling the insulation thickness of steel and plastic frames used in the electrical industry are also analyzed. Control of the insulation thickness after winding increases the amount of waste thermal insulation from expensive materials (for example, glass insulation), eliminating the identified violations is rather time-consuming and can make products unusable. Therefore, automation of the insulation thickness control process during winding has always been a difficult but urgent task. The solution to this problem can eliminate manual labor, reduce waste and improve the quality of industrial products used in the electrical and radio engineering industries. Operation principles, physical models and applications of various types of electromagnetic transducers of non-electrical quantities to electrical ones are considered. Features and characteristics of the main types of electromagnetic transducers of the insulation thickness of frames are analyzed. The characteristics of the main types of electromagnetic transducers of the thickness of glass insulation of frames are compared, their relative advantages and disadvantages are shown. Based on the analysis of the appropriate methods for controlling the thickness of various elements, problems are identified in the automation of insulation thickness control of plastic and steel frames in the winding process. Comparative analysis of the designs and characteristics of existing transducers shows that it is necessary to improve the design of linear induction levitation-screen suspensions and create effective methods of transmitting displacements to the levitation screen. Then the obtained unconventional designs can be successfully used for automatic control of the insulation thickness during winding it on rotating frames. For this purpose, differential inductive and transformer transducers with levitation screens and moving measuring windings are recommended. These transducers provide the required measurement accuracy, unambiguous continuous conversion of the insulation thickness into an electric signal in the winding process.